Risk Taking and Bank Failure Before and After the Onset of the Financial Crisis – A Decade in Review - Trendowski, Joseph; Rustambekov, Elzotbek (Journal of Applied Business and Economics, 2017)
At the beginning of the 21st century, financial institutions were achieving success through risk seeking behavior. While the economy was expanding, many negative consequences of risk were not realized. This study examines firm level factors of banks leading up to and continuing into the onset of the 2008 financial crisis and finds different results before and after the crisis. We test effects of geographic diversification and risk seeking behavior. Our evidence suggests that geographic diversification has no association with bank failure while risk seeking behavior has strong positive association with bank failure at the onset of the financial crisis.